International and National Security: Politics, Information, Ecology, Economy - Boiar, A.; Czop, A.; Fedoniuk, S.; Fesyk, O.; Karpchuk, N.; Kaźmierczak, D.; Khomiuk, N.; Kolomechiuk, V.; Kopachinska, G.; Kytsyuk, I.; Mykhailiuk, N.; Mytko, A.; et al. (MPBP “Hordon”, 2018)
The collective monograph is aimed at defining a coherent understanding of the current state of international information, environmental and economic security. It is intended for a wide range of specialists in international information, professionals working in structural subdivisions of state authorities, in information and analytical departments of local authorities and administration, in Public Relations departments of state and private structures, and others
Keywords: international Security; politics; information; ecology; 327(100)-049.5:351.746.1